Assessment of local mechanical properties of laser powder bed fused aluminium alloy by non-destructive testing based on FIMEC indentation - Vittorio Villani; Gennaro Salvatore Ponticelli; Simone Venettacci; Stefano Guarino (Acta Polytechnica CTU Proceedings)
Laser powder bed fusion process is a versatile metal additive manufacturing process. Although significant progress has been made so far, there is still limited large-scale adoption of this technique by the industry. The main problems are repeatability and lack of proper knowledge. In this work, an innovative and non-destructive testing methodology, based on flat-top cylinder indentation, was used to define the mechanical properties of laser powder bed fused aluminium alloy to highlight any variations induced by the combination of process parameters, for global characterization, and by the building direction, for local characterization. Results show similar or improved global mechanical properties of the laser powder bed fused specimens when compared to traditional die-casted ones. Indentation tests highlight a local dependence of properties along the building direction in favor of the upper part of the samples.